Overview of Financial Market Structures in Asia - Cases of the Republic of Korea, Malaysia, Thailand and Indonesia - Sayuri Shirai (Asian Development Bank Institute (ADBI), 2001)
This paper undertakes an overview of the financial structures in the Republic of Korea, Malaysia, Thailand, and Indonesia. It stresses that while the Asian countries have lowered their dependence on bank loans, especially since the crisis, the banking sector has remained dominant. Given the fact that alternative financing sources have been limited and unstable, it suggests that commercial banks will continue to be dominant financial institutions, and to act as major financiers for the economy, in the foreseeable future.
hdl:11540/4130
Keywords: 330